Survey of Interest in Learning Football at Public Junior High Schools in Topos District, Lebong Regency - Sudarmono Sudarmono; Supriyanto Supriyanto; Martiani Martiani (Penerbit Jurnal Indonesia, 2022)
This study aims to determine how much students' learning interest in soccer at the State Junior High School in Topos District, Lebong Regency. This type of research is descriptive qualitative research. Population and sample of State Junior High School students in Topos District, Lebong Regency. The number of students is 30 students. The results of interest in learning football at public junior high schools in the Topos sub-district, Lebong Regency, were categorized as very good, namely 4 people (13%), good category, namely 9 people (30%), and sufficient category, namely 12 people (40%), and poor category, namely 5 people (17%), and the very low category is 0 people (0%). Based on the results above, it can be concluded that the interest in learning football at the State Junior High School in the Topos District, Lebong Regency as a whole is in the sufficient category..